Caste, social inequality and mobility in rural India : reconceptualizing the Indian village - Sharma, K L (Sage, 2019)
Caste, Social Inequality and Mobility in Rural India: Reconceptualising the Indian Village investigates and presents a holistic view of today’s rural India by analysing different social aspects such as caste, migration, mobility, education and inequalities. It further studies the village social structure comprising peasants, artisans, weavers and the middle class, and the role of education in reshaping the social life of rural people. It challenges current conceptualisation and understanding of caste as a system, caste mobility, caste–class polarity and country–town divide. This book also argues that caste as a system has ceased to exist, but caste persists discretely as a non-systemic means of appropriation for political and social ends. This interdisciplinary dynamic study reconceptualises the ‘village’ by explaining the emerging social trends and patterns of social stratification in contemporary rural India.